LOCAL BUDGET EXPENDITURE AND THEIR STRUCTURAL ANALYSIS - qizi, Primova Nigora Ikrom (The journal of contemporary issues in business and government, 2021)
This article explores the importance of budget spending in public administration and economics. The significance of budget expenditures from the point of view of public administration, the purpose of funds accumulated in the budget from taxes and other funds is analyzed. According to the study, the state budget is based on the fact that production costs have a larger multiplier effect on GDP growth. Within the framework of the financial strategy of local budgets, proposals were formed on the possibility of reforms not only at the local budget level, but also at the state budget level.